The Strategic Foundation for Competitive Excellent Development in Integrated Islamic Primary Schools in Indonesia - Hifza, Juliana, Arika Palapa, Maskur, Aslan (International Journal of Advanced Science and Technology, 2020)
This qualitative study analyzes the strategic foundation of developing competitive excellence in integrated Islamic elementary schools in Indonesia. A qualitative approach was used for this multi-site design study. To collect the data, this study used in-depth interview, observation, and documentation techniques. While the data analysis was done by single site analysis and cross site analysis. The finding showed that the strategic foundations for developing competitive excellence in two integrated Islamic elementary schools are: First, religious motivation; to carry out the activities of educational institutions to the fullest in accordance with the concept of Islamic teachings. Second, the internal interests of the school; to improve the quality and image of the institution. Third, the external interests of the school; to meet the expectations and demands of the community towards the existence of superior and competitive Islamic educational institutions. Therefore, future studies analyzing the competitive integrated Islamic primary schools that exist in other institutions in the regions is needed to see challenges in achieving their excellence balance between islamic education competitive and its values for community.